DESENVOLVIMENTO DE MÉTODO PARA MAPEAMENTO SONORO DA CIDADE DE SÃO PAULO - Sales, Elisa Morandé; Brito, Adriana; Akutsu, Maria; Aquilino, Marcelo de Mello (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
There were developed procedures for noise mapping in great Brazilian cities based on European Directive 2002/49/EC. This Directive was adapted to the characteristics of the Brazilian Cities. There is presented a case study for the city of São Paulo. There are presented images of noise maps, cross sections and 3D elevations.